Proceedings of the 2nd International Conference of Continental Ichnology (ICCI 2017), Nuy Valley (Western Cape Winelands), 1–8 October 2017 - Bordy, Emese M (Evolutionary Studies Institute, 2018)
The 2nd International Conference of Continental Ichnology (ICCI 2017) was held in Nuy Valley (Western CapeWinelands) and followed by a field trip across South Africa to Lesotho from 1st to 8th of October 2017. The conference was dedicated to the study of continental trace fossils, and delegates presented research that focused on investigating various ichnofossils such as burrows, nests, tracks and trails. These are important not only for detailed characterization of past depositional environments, recognition of unconformities, prospecting for hydrocarbon resources, and biostratigraphic subdivisions, but also for the direct link they provide to ancient animal behaviour. The conference was organized by Dr Emese M. Bordy and the postgraduate students of her Sedimentology–Palaeontology Group at University of Cape Town (UCT), and was attended by 50 international delegates from Canada, U.S.A., Uruguay, Argentina, France, Germany, Sweden, Switzerland, Russia, Spain, U.K., Italy, Poland, South Africa and Lesotho (Fig. 1). This proceedings volume reflects the calibre and experience of the ICCI 2017 attendees, who appeared to be an ideal mix of senior and junior scientists. One third of the delegates were postgraduate students, and about of quarter of them were international students. We hope that all of you will enjoy the scientific content of this proceedings volume, which, among others, aims to showcase some of the best continental ichnological work globally and demonstrate why southern Africa is not only an exquisite geological and palaeontological wonder but also a world class ichnological research destination. The abundance and often uniqueness of the continental trace fossils in southern Africa are in stark contrast with the slow and punctuated development of ichnology in the region, even though the recognition and utilization of animal traces have been actively practiced here since prehistoric times. Cave paintings from the pre-1800s indicate that the indigenous hunter-gatherer San people, who have legendary neoichnological expertise, developed an early interest in the rich palaeoichnological record of the region and attempted to interpret ancient trace-making organisms (Ellenberger et al. 2005). Fascination with trace fossils and the identification of the producers by layman have also been recorded, among others, in the Western Cape (South Africa), where local farmers interpreted some Ordovician eurypterid tracks as footprints of ancient tortoises (Fig. 2A – Braddy & Almond 1999). The incorrect identification of trace fossils, which seems to be one of the most persistent traits of ichnology, is also associated with the first written record of a southern African trace fossil (later named Plagiogmus, a vermiformmetazoan trace – Fig. 2B) originally reported as impressions of fossil eels by H. Lichtenstein in his diary in 1803 (Macrae 1999; Master 2010). The first published record of invertebrate ichnofossils appeared in press nearly 70 years later as ‘trails of worms and tracks of Crustacea’ found in the Permian Ecca Group on Schietfontein farm (near Carnarvon) (Dunn 1872). Although vertebrate tracks were recorded in southern Africa in the late 19th century (?Dicynodon tracks in South Africa by Holub 1881; bird or lizard trackways in Lesotho by Dieterlen 1885 and Christol 1897), the first mention of invertebrate ichnofossils (Spirophyton) as fairly reliable stratigraphic markers has only been published in southern Africa in the early 20th century (Rogers 1905), after the ‘Age of Fucoids’ and well into the ‘Period of Reaction’ in European history of trace fossil studies. In these early days, Spirophyton was attributed to fucoids (remains of marine algae) or inorganic processes (Rogers 1905; Hatch & Corstorphine 1905) and impressions of seaweed of screw-like form(Schwarz 1912). Its first acceptable interpretation was given almost half of a century later as fossil traces of burrowing worms (Du Toit 1954). Following a slow start, ichnology in southern Africa only developed into an established discipline that links geology, sedimentology and palaeontology during the early 1970s and 1980s. This period is marked by the publication of the first detailed ichnofossil descriptions, ichnotaxonomic treatments and ichnologically based biostratigraphic and palaeoecological reconstructions. This golden era of southern African ichnology is primarily featured in internationally acclaimed contributions by Ann Anderson (Palaeozoic invertebrate ichnofossils, South Africa), Paul Ellenberger (Mesozoic vertebrate tracks, Lesotho), and Gerald Germs (Precambrian and Cambrian invertebrate ichnofossils, Namibia and South Africa). These active years also led to pioneering application of ichnofossils (in conjunction with lithofacies assemblages) to sedimentary facies analysis and interpretation (e.g. palaeobathymetry, marine vs non-marine settings) and incorporation of neoichnological studies in trace fossil interpretations (see works by D.K. Hobday, T.R. Mason, R. Shone, R.M.H. Smith, I.G. Stanistreet, I. Rust, B.R. Turner). The sluggish progress of ichnology in southern Africa, possibly due to geoscientific preoccupation with Karoo vertebrates and economically important Archaean rocks (Mason 1985), appears to be transformed by renewed interest in ichnological research in recent decades. We trust that the transformation has been spurred on by ICCI 2017, which injected even more rigour and enthusiasm into our local research community and offered all attendees opportunities to share and exchange ideas and to foster networking among potential collaborators. Once again, enjoy reading this proceedings volume of Palaeontologia africana! On behalf of the organizing committee: Emese M. Bordy
Keywords: footprints; trace fossils; terrestrial